Decision support system in kindergarten selection using TOPSIS method - Muslihudin M.; Ilayaraja M.; Sathesh Kumar K.; Shankar K.; Jamilah J.; Novitasari D.; Huda M.; Hashim W.; Rudenko I.V.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
Kindergarten is the most popular school in the world of early childhood, almost in every country put kindergarten into the most important schools for children's education. In Indonesia many kindergartens have emerged as a place to hone children's skills from an early age. This makes the selection of kindergarten schools, especially in Pringsewu district, a matter that is quite difficult to do, especially the lack of a website about each kindergarten school that is still lacking. Therefore, the authors conducted a research on how to create a system to assist in the selection of kindergartens using TOPSIS method, with the aim that people who want to find information about kindergarten can easily access it. Likewise with users who want to get a choice of kindergarten in accordance with their wishes. The TOPSIS method is chosen because the method is simple, easy to understand, the computation is efficient and has the ability to measure the relative performance of decision alternatives in a simple mathematical form. BEIESP.